Efl Learner's Perception on the Use of Mentimeter Platform in Enhancing Speaking Skills in Pohuwato - Samad, Partiwi (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2023)
The education sector in particular of technology learning brings benefits in a number of ways. An up-to-date learning has become the norm for teaching and learning in digital era. Both teachers and students are given a challenge to fully support the success of the integrated learning. When presenting educational resources to their students, teachers need to employ a greater degree of innovation meanwhile students are urged to engage in frequent study on their own as independent and effective learners. Therefore, the purpose of this study is to ascertain the EFL learner’s perception on the use of Mentimeter platform and to figure out the advantages of using Mentimeter Platform in enhancing speaking skills performance. The qualitative descriptive approach has been chosen as the method of this study. The data were obtained from interview and questionnaire. The findings showed that there were some perceptions about using Mentimeter Platform in enhancing the EFL learners’ speaking skills. Mostly students in definitely thought that the implementation of Mentimeter platform could enhance their speaking competence and surprisingly it also greatly benefited to their advance speaking and translating abilities.